Insulin‐like growth factor‐1 activates PI3K/Akt signalling to protect human retinal pigment epithelial cells from amiodarone‐induced oxidative injury. (8th December 2017) - Liao, Rifang; Yan, Fengxia; Zeng, Zhuanping; Wang, Haitao; Qiu, Kaifeng; Xu, Jinying; Zheng, Wenhua
Abstract : Background and Purpose: Amiodarone is one of the most effective anti‐arrhythmic drugs available, but its clinical applications are limited by toxic side effects including optic toxicity. The purpose of this study was to investigate the toxic effect of amiodarone on D407 cells (a human retinal pigmented epithelial (RPE) cell line) and the mechanisms of the protective effect of insulin‐like growth factor‐1 (IGF‐1). Experimental Approach: The involvement of the kinases, Akt and ERK, was analysed by Western blot. Intracellular accumulation of ROS was measured using fluorophotometric quantification. A pharmacological approach with inhibitors was used to investigate the pathways involved in the protective action of IGF‐1. Key Results: Amiodarone concentration‐dependently augmented the production of ROS, lipid peroxidation and apoptosis in D407 cells. IGF‐1 time‐ and concentration‐dependently reversed these effects of amiodarone and protected D407 cells from amiodarone‐mediated toxicity. Amiodarone inhibited the pAkt but not pErk, and IGF‐1 reversed this inhibitory effect of amiodarone. However, IGF‐1 failed to suppress amiodarone‐induced cytotoxicity in the presence of PI3K/Akt inhibitor LY294002 suggesting the direct involvement of the PI3K/Akt pathway. Furthermore, in vivo rat flash electroretinogram (FERG) recordings showed that IGF‐1 reverses the amiodarone‐induced decrease in a‐ and b‐waves. The immunocytochemistry findings confirmed that vitreous IGF‐1 injections promote the survival of RPE cells in rat retina treated with amiodarone. Conclusion and Implications: IGF‐1 can protect RPE cells from amiodarone‐mediated injury via the PI3K/Akt pathway in vivo and in vitro . IGF‐1 has potential as a protective drug for the prevention and treatment of amiodarone‐induced optic toxicity.